The use of histological methods to distinguish between burned remains of human and non-human bone - Sebolai, Masego Jessica (Department of Pathology, 2023)
As part of a medico-legal analysis it is necessary to identify if bone tissue is animal or human in nature. This process is complicated when bone is highly fragmented or burned. Previous research has established the ability to differentiate human from non-human bone histologically, however, further research is necessary to determine if this is still applicable in the case of burned remains. In South Africa, approximately 500 deaths and 15 000 fire related injuries occur annually in Cape Town and such fires ranged between 600°C to 1000°C. The aim of this research was to study the qualitative and quantitative characteristics of femur bone microstructure of human and animal bones exposed to different temperatures and to determine the possibility of distinguishing them. The study consisted of 17 femoral bone samples collected from four different species namely; humans (Homo sapiens), pig (Sus scrofa), wildebeest (Connochaetes gnou) and cow (Bos taurus). Unburned samples were compared to bone samples burned at 600°C, 700°C, 800°C and 900°C in a muffle furnace for 20 minutes. Bone samples were processed into thin sections for histological analysis. During analysis, each bone specimen was divided into four quadrants and two periosteal regions. For histomorphometric analysis, quantitative characteristics were assessed by measuring the area, perimeter, and minimum and maximum diameter of the Haversian system and Haversian canals as well as osteon circularity and osteon density. According to the qualitative results, the main structural bone tissue observed in all quadrants and two periosteal regions of unburned animal bone was primary vascular plexiform bone and irregular Haversian bone. Human bone consisted of dense Haversian bone. Quantitative results indicated a statistically significant difference in most parameters between species within burned as well as unburned samples (p<0.001). Statistically significant differences in quantitative parameters within human and wildebeest bone were noted at different burn temperatures (p<0.001). Overall, the results showed that heat exposure to bones can affect the bones' quantitative and qualitative characteristics but human and non-human bones can still be differentiated. This histological method can be used in forensic fire cases.